Nano coating for radiator, coating and preparation method thereof
By using nanocoats prepared by nano-scale terminal hydroxyl liquid rubber and melamine resin on the radiator, the problem of poor coating performance of traditional radiator materials is solved, and the effects of high mechanical strength, thermal stability and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510256828.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
Traditional radiator materials and their coatings have problems such as insufficient durability, poor wear resistance, weak thermal conductivity, insufficient chemical resistance and corrosion resistance, resulting in poor performance and durability.
Using nano-grade terminal hydroxyl liquid rubber and melamine resin and other raw materials, a nanocoat for radiator with a thickness controlled between 9 and 15 μm is prepared, which significantly improves the physical and chemical properties and adhesion of the coating.
The coating is achieved with high mechanical strength, thermal stability, good corrosion resistance and wear resistance, significantly improving the performance and durability of the radiator.
Smart Images

Figure CN119736004A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radiator coatings, and in particular is a nano coating for radiators, a coating and a preparation method thereof. Background Art
[0002] Nanostructured coatings are ultra-thin coatings that can significantly improve the surface properties of almost any material without changing the thermal conductivity or surface texture of the material. This type of coating enhances the surface properties of the material without changing its inherent properties or its chemical composition.
[0003] Nano-coating technology plays an important role in many fields such as biomedicine, engineering, military, energy, and aerospace, and has made significant contributions to the technological progress of these industries. Traditional materials and their coatings often have many limitations, such as insufficient durability, poor wear resistance, weak thermal conductivity, insufficient chemical and corrosion resistance, and reduced strength. Summary of the invention
[0004] In order to overcome the above-mentioned technical problems, the present invention provides a nano-coating, a coating and a preparation method for a radiator. The thickness of the nano-coating for the radiator of the present invention is controlled at 9-15 μm, and the physical and chemical properties of the coating are significantly improved through optimized formula and process flow; in addition, the coating exhibits excellent stability and adhesion, which are crucial for improving the performance and durability of the radiator.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The invention discloses a nano coating for a radiator, comprising the following raw materials in parts by weight: 40-70 parts of polyester resin, 2-15 parts of liquid rubber, 0-50 parts of thermosetting acrylic resin, 8-20 parts of melamine resin, 0-15 parts of blocked isocyanate, 0.5-2 parts of leveling agent, 0.5-1.2 parts of dispersant, 0.2-1.5 parts of defoamer, 0.2-1.5 parts of drying agent and 25-45 parts of organic solvent; The polyester resin is a polar polyester resin containing hydrogen bonds; The liquid rubber is a hydroxy-terminated nitrile liquid rubber; wherein the liquid rubber is a material with multiple hydrogen bonds and strong polarity that can undergo addition polycondensation reaction, and this material has good mechanical properties, so it can be made into a wear-resistant, high-strength, and corrosion-resistant coating; The organic solvent is a mixed solvent of petroleum ether, propylene glycol methyl ether acetate and n-butanol.
[0007] Preferably, the nano coating for radiator comprises the following raw materials in parts by weight: 40-65 parts of polyester resin, 2-10 parts of liquid rubber, 0-50 parts of thermosetting acrylic resin, 8-16 parts of melamine resin, 0-15 parts of blocked isocyanate, 0.5-2 parts of leveling agent, 0.5-2 parts of dispersant, 0.2-1 parts of defoamer, 0.2-1 parts of drying agent and 25-40 parts of organic solvent; More preferably, the nano coating for radiator comprises the following raw materials in parts by weight: 40-50 parts of polyester resin, 5-8 parts of liquid rubber, 0-20 parts of thermosetting acrylic resin, 10-15 parts of melamine resin, 0-15 parts of blocked isocyanate, 0.5-0.8 parts of leveling agent, 0.8-1 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.2-0.5 parts of drying agent and 25-35 parts of organic solvent.
[0008] The material of the radiator is aluminum alloy; preferably, the material of the radiator is 1 series aluminum alloy, 5 series aluminum alloy or 6 series aluminum alloy; more preferably, the material of the radiator is 1050 aluminum alloy, 3003 aluminum alloy, 5038 aluminum alloy, 6061 aluminum alloy, 6063 aluminum alloy, 6082 aluminum alloy or 7075 aluminum alloy; for example, the material of the radiator is 5038 aluminum alloy or 6082 aluminum alloy.
[0009] In the present invention, the melamine resin is hexamethoxymethyl melamine resin.
[0010] In the present invention, the leveling agent is polydimethylsiloxane containing epoxy functional groups.
[0011] In the present invention, the blocked isocyanate is a blocked alicyclic polyisocyanate.
[0012] In the present invention, the dispersant is a polydimethylsiloxane modified with organosilicon. This auxiliary agent effectively enhances its oil-repellent and water-repellent properties by cross-linking with the hydroxyl groups in the system, thereby improving the easy-to-clean effect of the modified adhesive. This auxiliary agent can reduce the viscosity of the system, improve the stability of the nanoparticles, and prevent particle flocculation, which is crucial to improving the storage stability of the final product.
[0013] In the present invention, the organic solvent is petroleum ether: propylene glycol methyl ether acetate (PMA): n-butanol in a mass ratio of 30-50:30-40:10-40, for example, 50:30:20.
[0014] The petroleum ether model is 150#.
[0015] In the present invention, the hydroxyl content of the polyester resin is 15-25 mg KOH / g.
[0016] In the present invention, the solid content of the polyester resin is ≥60%.
[0017] In the present invention, the polyester resin has a viscosity of 13000-17000 mPa·s at 25°C.
[0018] In the present invention, the Mw of the polyester resin is ≥2000.
[0019] In the present invention, the solid content of the liquid rubber is ≥98%.
[0020] In the present invention, the hydroxyl content of the liquid rubber is 31-42 mg KOH / g.
[0021] In the present invention, the viscosity of the liquid rubber at 40° C. is ≤25 mPa·s.
[0022] In the present invention, the solid content of the melamine resin is ≥98%.
[0023] In the present invention, the viscosity of the melamine resin at 23° C. is 3000-6200 mPa·s.
[0024] In the present invention, the viscosity of the thermosetting acrylic resin is 3000-5000 mPa·s.
[0025] Among them, adding thermosetting acrylic resin to the coating can enhance the hardness, adhesion, cooking resistance and solvent resistance of the coating.
[0026] In the present invention, the viscosity of the blocked isocyanate is 4500-6500 mPa·s.
[0027] In the present invention, the NCO content of the blocked isocyanate is 7.5-8.5wt%.
[0028] Blocked isocyanates have excellent reactivity and storage stability, fast drying, and water and chemical resistance.
[0029] The present invention also discloses a method for preparing the nano coating for radiator, which comprises the following steps: mixing the preparation raw materials to obtain the nano coating for radiator.
[0030] Wherein, the mixing comprises the following steps: S1. Add a dispersant, a polyester resin, a liquid rubber, a melamine resin, a thermosetting acrylic resin, a blocked isocyanate, and a leveling agent to an organic solvent and stir to obtain a first solution; S2. Add an organic solvent to the first solution and mix well, then let stand to obtain a second solution; S3. After adding a defoamer and a drying agent to the second solution and stirring, a nano-coating for a radiator is obtained; In S1, the stirring speed is 1000-1500 rpm, for example, 1200 rpm.
[0031] In S1, the stirring time is 30 to 50 minutes.
[0032] In S2, the standing time is 15 to 50 minutes, for example, 30 minutes.
[0033] In S3, the stirring speed is 500-800 rpm.
[0034] In S3, the stirring time is 10 to 15 minutes.
[0035] After the mixing, the mixture needs to be sieved through a 120-200 mesh sieve.
[0036] The invention discloses a nano coating for a radiator, and the raw materials for preparing the nano coating include the above-mentioned nano coating for a radiator.
[0037] In the present invention, the thickness of the nano coating for heat sink is 9-15 μm; in the present invention, the glossiness of the nano coating for heat sink is >20°, preferably 20°-25°, and more preferably 22-23°.
[0038] The present invention also discloses a method for preparing the aforementioned nano coating for radiator, comprising the following steps: coating the coating on the surface of the radiator to obtain the nano coating for radiator.
[0039] The coating method is dipping, spraying or showering; preferably, the coating method is spraying.
[0040] Furthermore, the spraying method is low-pressure spraying.
[0041] Furthermore, the caliber of the spray gun used for spraying is 0.8~1.0mm.
[0042] Furthermore, during the spraying, the distance between the nozzle and the radiator surface is 15-18 mm.
[0043] Furthermore, the spraying speed is 10-12 m / min.
[0044] The coating step also includes a curing step.
[0045] Furthermore, the curing temperature is 160-175°C.
[0046] Furthermore, the curing time is 30 to 40 minutes.
[0047] The nano paint or coating for radiator of the present invention is applied to the surface of metal heat exchanger.
[0048] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0049] Compared with the prior art, the present invention has the following beneficial effects: 1. The thickness of the nano coating for radiator of the present invention is in the range of 9 to 15 μm. The nano coating for radiator adopts a nano-scale hydroxyl-terminated liquid rubber with super hydrophobic and oleophobic properties. The hydroxyl active functional group of the liquid rubber can react with a polyester resin with multiple hydrogen bonds and strong polarity that can undergo addition polycondensation to form a stable covalent bond, and further react with a melamine resin during the curing process under high temperature conditions to construct a three-dimensional network structure. This process significantly enhances the crosslinking density of the coating and improves the compactness of the coating of the present invention.
[0050] 2. The nano coating for radiator of the present invention has strong adhesion and good comprehensive mechanical properties. In terms of hardness and high temperature resistance, the coating exhibits high mechanical strength and thermal stability, can adapt to high temperature environment and is not easily deformed or damaged. Its resistance to neutral salt spray shows that the coating has good corrosion resistance. The impact strength and wear resistance test results show that the coating can withstand large impact and friction forces and maintain surface integrity. In terms of chemical resistance, the coating shows good tolerance to both acids and alkalis. In addition, the coating's test results in boiling water resistance, salt water resistance and water resistance tests, as well as gasoline resistance, further confirm the coating's stable applicability in aqueous or oily media. The scrub resistance, butanone wiping resistance and alcohol wiping resistance properties show the coating's ability to resist damage when facing physical and chemical wiping. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The following are the appearance pictures of the nano coatings of Example 1 (A) and Comparative Example 1 (B) after the scrubbing resistance test.
[0052] Figure 2 This is the appearance of the nano coating of Example 11 after the salt spray test.
[0053] Figure 3 This is the appearance of the nano coating of Example 12 after the salt spray test. DETAILED DESCRIPTION
[0054] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0055] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0056] For information about the raw materials used in the following examples or comparative examples, please refer to Table 1.
[0057] .
[0058] Note: For the convenience of testing, the following examples and comparative examples all use aluminum alloy plates (75mm*150mm*0.8mm) instead of radiators for coating, and finally prepare samples, which include nano-coatings for radiators and aluminum alloy plates; the samples are subjected to subsequent tests.
[0059] Example 1 1. The nano coating for radiator of this embodiment includes the following raw materials by weight: 40 parts of polyester resin, 2 parts of liquid rubber, 8 parts of melamine resin, 0.5 parts of leveling agent, 0.5 parts of dispersant, 0.2 parts of defoaming agent, 0.2 parts of drying agent and 35 parts of organic solvent; The volume ratio of 150# petroleum ether:PMA:n-butanol in the organic solvent is 50:30:20.
[0060] 2. The method for preparing the nano coating and coating for the radiator of this embodiment comprises the following steps: S1. According to the above formula, 20 parts of organic solvent were added to the pull cylinder, and dispersant, polyester resin, liquid rubber, melamine resin and leveling agent were slowly added in sequence while maintaining stirring at 400rpm, and stirred at 1200rpm for 30min; The remaining amount of solvent was added and mixed, and then the mixture was allowed to stand for 30 minutes. Subsequently, the defoamer and the drying agent were slowly added while stirring at 400 rpm, and the mixture was stirred at 500 rpm for 15 minutes to obtain the nano coating for the radiator.
[0061] S2. Clean and degrease the surface of the aluminum alloy plate to remove the oxide layer to prevent dust, grease and rust stains on the radiator surface; then use low-pressure spraying, the spray gun diameter is 1.0mm, the nozzle distance to the surface of the aluminum alloy plate is specifically controlled within the range of 15~18mm, and the spraying speed is 10~12m / min; then cure at 170℃ for 35min to obtain the sample.
[0062] The aluminum alloy plate in this embodiment is made of 1050 aluminum alloy.
[0063] Example 2 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0064] In parts by mass, the preparation raw materials of this embodiment include 50 parts of polyester resin, 7 parts of liquid rubber, 15 parts of melamine resin, 5 parts of thermosetting acrylic resin, 7 parts of blocked isocyanate, 1 part of leveling agent, 0.7 parts of dispersant, 0.7 parts of defoaming agent, 0.7 parts of drying agent and 30 parts of organic solvent.
[0065] In the coating preparation process of this embodiment, thermosetting acrylic resin and blocked isocyanate are also added in the mixing process in S1. In the following embodiments and comparative examples, mixing is performed in the S1 process according to the formulation requirements.
[0066] Example 3 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0067] In parts by mass, the preparation raw materials of this embodiment include 45 parts of polyester resin, 12 parts of liquid rubber, 20 parts of thermosetting acrylic resin, 10 parts of melamine resin, 15 parts of blocked isocyanate, 1.5 parts of leveling agent, 1 part of dispersant, 1 part of defoaming agent, 1 part of drying agent and 40 parts of organic solvent.
[0068] Example 4 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0069] In parts by mass, the preparation raw materials of this embodiment include 40 parts of polyester resin, 7 parts of liquid rubber, 5 parts of thermosetting acrylic resin, 8 parts of melamine resin, 7 parts of blocked isocyanate, 1 part of leveling agent, 0.7 parts of dispersant, 0.7 parts of defoaming agent, 0.7 parts of drying agent and 30 parts of organic solvent.
[0070] Example 5 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0071] In parts by mass, the preparation raw materials of this embodiment include 50 parts of polyester resin, 12 parts of liquid rubber, 15 parts of thermosetting acrylic resin, 15 parts of melamine resin, 15 parts of blocked isocyanate, 1.5 parts of leveling agent, 1 part of dispersant, 1 part of defoaming agent, 1 part of drying agent and 30 parts of organic solvent.
[0072] Example 6 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0073] In parts by mass, the raw materials for preparation of this embodiment include 65 parts of polyester resin, 2 parts of liquid rubber, 20 parts of melamine resin, 0.5 parts of leveling agent, 0.5 parts of dispersant, 0.2 parts of defoaming agent, 0.2 parts of drying agent and 35 parts of organic solvent.
[0074] Example 7 The preparation raw materials of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0075] In parts by mass, the preparation raw materials of this embodiment include 40 parts of polyester resin, 12 parts of liquid rubber, 5 parts of thermosetting acrylic resin, 8 parts of melamine resin, 15 parts of blocked isocyanate, 1 part of leveling agent, 1 part of dispersant, 1 part of defoaming agent, 1 part of drying agent and 30 parts of organic solvent.
[0076] Example 8 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0077] In parts by mass, the preparation raw materials of this embodiment include 50 parts of polyester resin, 2 parts of liquid rubber, 15 parts of thermosetting acrylic resin, 15 parts of melamine resin, 7 parts of blocked isocyanate, 0.7 parts of leveling agent, 0.7 parts of dispersant, 0.7 parts of defoaming agent, 0.7 parts of drying agent and 40 parts of organic solvent.
[0078] Example 9 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0079] In parts by mass, the raw materials for preparation of this embodiment include 65 parts of polyester resin, 7 parts of liquid rubber, 20 parts of melamine resin, 1.5 parts of leveling agent, 0.5 parts of dispersant, 0.2 parts of defoaming agent, 0.2 parts of drying agent and 35 parts of organic solvent.
[0080] Example 10 The raw material formulas for the preparation of this embodiment are different from those of embodiment 1, and the other steps and parameters are the same as those of embodiment 1.
[0081] In parts by mass, the raw materials for preparation of this embodiment include 45 parts of polyester resin, 8 parts of liquid rubber, 10.5 parts of melamine resin, 0.6 parts of leveling agent, 1 part of dispersant, 0.5 parts of defoaming agent, 0.4 parts of drying agent and 34 parts of organic solvent.
[0082] Comparative Example 1 The raw material formula of this comparative example is different from that of Example 1, and this comparative example does not contain liquid rubber and thermosetting acrylic resin; other steps and parameters are the same as those of Example 1.
[0083] In parts by mass, the raw materials for the preparation of this comparative example include 60 parts of polyester resin, 12.5 parts of blocked isocyanate, 0.8 parts of leveling agent, 0.8 parts of dispersant, 0.8 parts of defoaming agent, 0.4 parts of drying agent and 35 parts of organic solvent.
[0084] Compared with Example 1, no liquid rubber and thermosetting acrylic resin are added in Comparative Example 1, so the solubility after mixing with the polyester in the coating is poor, the coating film becomes brittle, some properties do not reach the optimal state, conventional physical properties deteriorate, and salt spray resistance, wear resistance, chemical resistance and other properties are reduced.
[0085] Comparative Example 2 The raw material formula of this comparative example is different from that of Example 1, and this comparative example does not contain liquid rubber and blocked isocyanate; other steps and parameters are the same as those of Example 1.
[0086] The raw material formula for the preparation of this comparative example includes, by weight, 50 parts of polyester resin, 25 parts of thermosetting acrylic resin, 12.5 parts of melamine resin, 0.8 parts of leveling agent, 0.8 parts of dispersant, 0.5 parts of defoaming agent, 0.4 parts of drying agent and 34 parts of organic solvent.
[0087] Test Example 1 The samples of the above-mentioned embodiments 1 to 10 and comparative examples 1 to 2 were tested according to the standards or methods in Table 2.
[0088] The impact strength test means that after a heavy hammer falls freely, the paint film does not crack when it withstands a gravity of 50kg per square centimeter.
[0089] The coolant resistance test method is to place the samples prepared in each embodiment and comparative example in a coolant and heat them to 75° C. for 120 hours; after the coolant resistance test is completed, the appearance of the samples is observed to see if they are peeling, discolored, or damaged, exposing the base material.
[0090] The transformer oil resistance test method is to place the samples prepared in each embodiment and comparative example in a coolant and heat them to 125° C. for 120 hours; after the transformer oil test is completed, the appearance of the samples is observed to see whether they are peeled off, discolored, or damaged to expose the aluminum alloy plate.
[0091] The test results are shown in Tables 3 and 4.
[0092] .
[0093] .
[0094] .
[0095] Figure 1The following is a comparison of the appearance of Example 1 (A) and Comparative Example 1 (B) after 8,000 wash resistance tests. The test results show that after 8,000 washes, the nano coating of Example 1 had slight wear and scratches on the surface of the sample, but the coating was not damaged to expose the underlying aluminum alloy plate. In addition, the hydrophobicity, water drop angle, and scratch indicators of Example 1 only changed slightly compared to before the test, and the coating structure remained intact without damage.
[0096] In contrast, the nano coating of Comparative Example 1 exhibited obvious shedding and scratches under the same conditions, and the gloss loss rate after the washability test increased significantly.
[0097] Examples 10 to 12 explore the salt spray resistance test results when the samples are made of different series of aluminum alloy materials. For the convenience of testing, aluminum alloy plates are used instead of radiators for the experiments.
[0098] Embodiment 11 The aluminum alloy plate in this embodiment is made of 5038 aluminum alloy, and the other steps and parameters are the same as those in Embodiment 10.
[0099] Example 12 The aluminum alloy plate in this embodiment is made of 6082 aluminum alloy, and the other steps and parameters are the same as those in Embodiment 10.
[0100] Test Example 2 According to GB / T 6458 standard, the samples of Examples 11 and 12 were subjected to a neutral salt spray test.
[0101] The appearance of the samples of Example 11 after 3380h and 3480h of neutral salt spray test are respectively Figure 2 After 3380h of scratch neutral salt spray test, the gloss and hardness of the sample did not change. However, after 3480h, the appearance of the sample lost its gloss and the coating became soft.
[0102] The appearance of the samples of Example 12 after 3380h and 3480h of neutral salt spray test are respectively Figure 3 Similar to Example 1, the gloss and hardness of the sample remained unchanged after 3380 hours, but after 3480 hours, the sample also showed gloss loss and coating softening.
[0103] The radiator nano coating of the present invention shows good adhesion performance to 1 series, 5 series and 6 series aluminum alloys, indicating that it is suitable for various types of aluminum alloy materials, especially 5038 and 6082 aluminum alloys.
[0104] The present invention relates to a nano coating applied to a radiator, which is intended to replace traditional chromization and electrophoresis treatment methods. Compared with traditional treatments, this nano coating provides excellent long-lasting and easy-to-clean performance, while achieving a high-strength anti-corrosion effect, and can maintain corrosion resistance for 3000 to 4000 hours in a salt spray environment. In addition, the nano coating also has high-strength anti-wear and anti-scratch capabilities, enhances the texture effect of the metal, and enables the metal surface to remain clean and bright for a long time. Ultimately, the coating film is given a high-strength anti-corrosion function (salt spray resistance 3000-4000h), and also brings high-strength anti-wear, anti-scratch, chemical resistance, good mechanical and excellent appearance.
[0105] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A nano coating for a radiator, characterized in that: The preparation method comprises the following raw materials in parts by weight: 40-70 parts of polyester resin, 2-15 parts of liquid rubber, 0-50 parts of thermosetting acrylic resin, 8-20 parts of melamine resin, 0-15 parts of blocked isocyanate, 0.5-2 parts of leveling agent, 0.5-1.2 parts of dispersant, 0.2-1.5 parts of defoaming agent, 0.2-1.5 parts of drying agent and 25-45 parts of organic solvent; The polyester resin is a polar polyester resin containing hydrogen bonds; The liquid rubber is a hydroxy-terminated nitrile liquid rubber; The organic solvent is a mixed solvent of petroleum ether, propylene glycol methyl ether acetate and n-butanol.
2. The nano coating for radiator according to claim 1, characterized in that: Meet at least one of the following conditions ①~④: ① The melamine resin is hexamethoxymethyl melamine resin; ② The leveling agent is polydimethylsiloxane containing epoxy functional groups; ③ The blocked isocyanate is a blocked alicyclic polyisocyanate; ④ The dispersant is silicone-modified polydimethylsiloxane.
3. The nano coating for radiator according to claim 2, characterized in that: Satisfy at least one of the following conditions ①~⑨: ① The hydroxyl content of the polyester resin is 15-25 mg KOH / g; ②The solid content of the polyester resin is ≥60%; ③ The viscosity of the polyester resin at 25° C. is 13000-17000 mPa·s; ④ The Mw of the polyester resin is ≥ 2000; ⑤The solid content of the liquid rubber is ≥98%; ⑥ The hydroxyl content of the liquid rubber is 31-42 mg KOH / g; ⑦ The viscosity of the liquid rubber at 40°C is ≤30 mPa·s; ⑧ The solid content of the melamine resin is ≥98%; ⑨ The viscosity of the melamine resin at 23° C. is 3000-6200 mPa·s.
4. The method for preparing a nano coating for a radiator according to any one of claims 1 to 3, characterized in that: The following steps are involved: The prepared raw materials are mixed to obtain a nano coating for a radiator.
5. The method for preparing the nano coating for radiator according to claim 4, characterized in that: Meet at least one of the following conditions ①~②: ① The mixing comprises the following steps: S1. Add a dispersant, a polyester resin, a liquid rubber, a melamine resin, a thermosetting acrylic resin, a blocked isocyanate, and a leveling agent to an organic solvent and stir to obtain a first solution; S2. Add an organic solvent to the first solution and mix well, then let stand to obtain a second solution; S3. After adding a defoamer and a drying agent to the second solution and stirring, a nano-coating for a radiator is obtained; ② After mixing, pass through a 120-200 mesh sieve.
6. A nano coating for a radiator, characterized in that: The raw materials for preparing the nano coating include the nano coating for radiator as described in any one of claims 1 to 3.
7. The nano coating for heat sink according to claim 6, characterized in that: The thickness of the nano coating for the heat sink is 9-15 μm.
8. The method for preparing a nano coating for a radiator according to any one of claims 6 to 7, characterized in that: The following steps are involved: The nano coating for the radiator is obtained by coating the coating on the surface of the radiator.
9. The method for preparing a nano coating for a heat sink according to claim 8, characterized in that: Meet at least one of the following conditions ①~②: ① The coating method is dipping, spraying or showering; ② After the coating, a curing step is also included.
10. The method for preparing a nano coating for a heat sink according to claim 9, characterized in that: Meet at least one of the following conditions ①~⑤: ① The caliber of the spray gun used for spraying is 0.8~1.0mm; ② The distance between the spray nozzle and the radiator surface is 15-18 mm; ③ The spraying speed is 10~12m / min; ④ The curing temperature is 160~175°C; ⑤The curing time is 30 to 40 minutes.
Citation Information
Patent Citations
Insulating and heat-radiating coating composition, and insulating and heat-radiating product implemented therewith
CN109563361A
Common alumite color layer coating capable of being rapidly cured at low temperature and preparation method of common alumite color layer coating
CN116656199A
Paint composition and manufacturing method thereof
KR1020160078097A
Ec0-friendly two-component paint composition and construction method using the same
KR102282703B1
Coating composition with high solids content, and method for forming multilayer coating film
US20230257618A1